The Effect of Using Dynamic Geometry Software on The Success of Geometry: A Meta-Analysis Study - Berna Cantürk Günhan, Hatice Açan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2016)
This study evaluates with the meta-analysis method that is defined as a systematic review of experimental studies the results of the dynamic geometry software applied in Turkey in the last nine years and analyzes the effect of using dynamic geometry software on the success of geometry. In order to access these studies, the YÖK National Thesis Center, Ulakbim and Google Scholar databases were reviewed. As a result of a survey of the literature of dynamic geometry software a total of 41 studies on the effect on students' achievements in geometry were included in the meta-analysis. An effect size value of 43 was calculated from these studies. As a result of necessary analyses, it was concluded that using dynamic geometry software in Turkey is more successful than ongoing education and the calculated effect size of 0.954 is at a strong level. Comparative effect sizes according to education level, application duration, sample size and publication size were calculated and it was discovered that effect size on academic success does not differ according to education level, application duration, sample size and publication size. According to the results obtained in the study, recommendations were made to researchers.